Role of impregnated lubricant in enhancing thermosyphon performance. (June 2017) - Zhang, P.; Lv, F.Y.; Askounis, A.; Orejon, D.; Shen, B.
Highlights: The SLIPS accelerates the removal of condensed droplets. The SLIPS condenser significantly enhances the condensation heat transfer. The SHi evaporator alleviates the influence of lubricant on boiling heat transfer. The total thermal resistance of the TPCT-SHiSL is remarkably reduced. The TPCT-SHiSL shows good durability. Abstract: We report on the optimal configuration for enhanced heat transfer performance of a two-phase closed thermosyphon (TPCT), incorporating a superhydrophilic (SHi) evaporator with a slippery lubricant-infused porous surface (SLIPS) condenser (TPCT-SHiSL). For the conditions examined, the overall heat transfer performance of the TPCT-SHiSL was enhanced by as much as 28.9% compared to the other configurations proposed. This enhancement is attributed to the use of SLIPS as the condenser, which promotes the condensation heat transfer and the overall heat transfer performance. Moreover, we illustrate the importance of pairing the SLIPS condenser with a SHi evaporator, in order to minimize lubricant absorption at the evaporator. Additionally, the heat transfer performance of the TPCT-SHiSL was evaluated over time and consistent results were observed even after 16 experimental runs (192 h in 90 days), demonstrating good durability of the TPCT-SHiSL.